Economic challenges and success in the post-COVID era: A CAGE Policy Report (2021)
In 2008 there was an expectation of major reform to social and economic structures following the financial crisis. The European Union (EU) referendum of 2016, and the UK’s subsequent exit from the EU in 2020, was also signalled as a turning point that would bring about epochal change. Now, in the waning of the coronavirus pandemic, we are experiencing a similar rhetoric. There is widespread agreement that the pandemic will usher in big changes for the economy and society, with the potential for major policy reform. But what will be the long-term impacts of the pandemic on the UK economy? Is the right response a “new settlement” or is some alternative approach likely to be more beneficial?This report puts forward a new perspective on the pandemic-related changes that could be ahead. The central theme is assessing the viability of epochal reform in policymaking. There seems to be a relentless desire for making big changes; however, there is arguably not enough recognition of how current settings and history can hold back these efforts.Foreword by:  Dame Frances Cairncross, CBE, FRSE.